RELATIONSHIP OF LOW BIRTH WEIGHT, NUTRITIONAL STATUS AND EXCLUSIVE BREAST-FEEDING WITH ARI IN INFANTS AGED 6–23 MONTHS IN KARANG ASAM PUBLIC HEALTH CENTER, SAMARINDA CITY IN 2018 - Magdaleni, Agustina Rahayu; Irawan, Dimas Bagus; Sukemi, Sayidi (JURNAL ATOMIK, 2020)
Acute respiratory infection (ARI) is one of the main causes of patient visits (40%–60%) in public health centers from year to year and is always on the list of the 10 most diseases each year in health facilities, such as health centers. Populations susceptible to ARI are children less than two years old who have health problems such as malnutrition, have a history of low birth weight (LBW), do not get exclusive breastfeeding. The aim of this research is to find out the relationship between LBW, nutritional status and exclusive breastfeeding with ARI in infants aged 6–23 months in Karang Asam Public Health Center in 2018. This research is quantitative research with a design cross-sectional. The study was conducted on 87 samples, namely toddlers aged 6–23 months who visited and registered at Karang Asam Public Health Center. The sample was taken by accidental sampling. Bivariate analysis using the Chi-Square test showed a significant correlation between nutritional status and ARI in infants aged 6–23 months (0.026) and between exclusive breastfeeding and ARI in infants aged 6–23 months (0.005). Whereas there was no association between LBW and ARI in infants aged 6–23 months at Karang Asam Public Health Center in 2018 (0.078). It can be concluded that there are significant relationships between nutritional status and exclusive breastfeeding with ARI in infants aged 6–23 months. In contrast to LBW, there is no association between LBW and ARI in infants aged 6–23 months in Karang Asam Public Health Center in 2018